Website Based Respiratory Diseases Diagnosis Expert System Using Forward Chaining Method - Widad, Achmad; Susano, Adhi; Rahmi Pinahayu, Ek Ajeng (Edusight International Journal of Multidisciplinary Studies, 2024)
This research aims to produce a website based expert system application that can diagnose respiratory diseases in humans. This research was conducted at the Tegal Parang sub-district health center using the forward chaining method. The forward chaining method is used to monitor the process of drawing conclusions in the expert system being built. The research stages carried out included an interview process with doctors and then analyzed using the forward chaining method. The forward chaining method was chosen because of its ability to provide accurate and easy to understand results by starting from existing facts and applying rules to reach conclusions. This method is very effective in expert systems for diagnosing respiratory diseases because it allows the process of drawing logical and systematic conclusions based on the initial data provided. This application was developed using HTML, PHP, JavaScript, CSS, and Bootstrap as programming languages, and MySQL for database management. The research results show that this application increases efficiency in data collection and reporting, makes it easier for medical personnel to manage patient data with a user-friendly interface, and manages diagnosis data in a computerized manner, thereby reducing human error and increasing efficiency. It is hoped that this research can make a significant contribution in simplifying the process of diagnosing respiratory diseases and improving the quality of health services at the Tegal Parang sub-district health center.